Movilización, política y nación. Una aproximación historiográfica a los cultos marianos en época contemporánea - Francisco Javier Ramón Solans (Amnis)
The aim of this paper is to report the most interesting contributions to the study of Marian devotions in contemporary times. First, we highlight that a good part of the studies have stressed the political role played by these cults. On this subject, we will also address the important ability to mobilize and the use of modern repertoires in their development. Second, we focus on the important role played by these cults in the construction of national identity. Finally, we take a brief historiographical balance of Marian cults studies in contemporary Spain.